The IEFG: role of a philanthropic affinity network within global education (2019)
If you were lucky enough to have the funds, how would you start on your journey to good grant-making in education? How would you go about choosing a project on which to focus? How would you measure your achievements and those of your grantees? How would you keep up with new developments and research in the education field? How would you find a group of peers to share ideas with, knowing that when you open your mouth at an education conference, or to a non-governmental organisation (NGO), that the expectation of money looms in the background? How could you ensure your work is not done in isolation but serves to strengthen the education sector and move the field forward?